Researching translation and interpreting - Angelelli, Claudia; Baer, Brian James (Routledge, Taylor & Francis Group, 2016)
This volume offers a comprehensive view of current research directions in Translation and Interpreting Studies, outlining the theoretical concepts underpinning that research and presenting detailed discussions of the various methods used.